2020
DOI: 10.3390/ijerph18010205
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gene Polymorphisms of Vitamin D Receptor and Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: (1) Background: Studies on the association between Vitamin D receptor gene polymorphism and gestational diabetes mellitus have been inconsistent. The aim of this study was to summarize available evidence on the association between polymorphisms of Vitamin D receptor genes and susceptibility to gestational diabetes mellitus. (2) Methods: We searched databases of PubMed, Web of Science, Embase, China national knowledge infrastructure (CNKI), China science and technology journal database (VIP), and Wanfang Data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…Our study found that the increasing level of vitamin D nutritional status in pregnancy is significantly related to reducing the incidence of GDM. Vitamin D deficiency is a risk factor for GDM, consistent with some existing reports that maternal early pregnancy serum level of 25-Hydroxyvitamin D and risk of gestational diabetes mellitus [ 33 36 ]. The reason may be that vitamin D takes part in glucose homeostasis, and the mechanism possibly refers to insulin secretion and insulin action [ 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our study found that the increasing level of vitamin D nutritional status in pregnancy is significantly related to reducing the incidence of GDM. Vitamin D deficiency is a risk factor for GDM, consistent with some existing reports that maternal early pregnancy serum level of 25-Hydroxyvitamin D and risk of gestational diabetes mellitus [ 33 36 ]. The reason may be that vitamin D takes part in glucose homeostasis, and the mechanism possibly refers to insulin secretion and insulin action [ 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, our follow-up results showed that 43 of the 104 GDM patients had adverse pregnancy outcomes. GDM can cause vascular disease and abnormal energy metabolism, which enables the fetus to absorb too much sugar, resulting in larger than average babies, an increased risk of delivery, and ultimately a series of adverse outcomes (17,18). To clarify the risk factors affecting the pregnancy outcomes of GDM patients, this study tested the levels of glycosylated hemoglobin, vitamin A, vitamin E, MDA, SOD, GSH, and TAOC in the two groups and found that the expression levels of glycosylated hemoglobin, vitamin A, vitamin E, MDA, SOD, GSH, and TAOC were independent risk factors affecting the pregnancy outcomes of GDM patients (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VDR and vitamin D-metabolising enzymes have been found to be strongly expressed in pancreatic beta cells and insulin-responsive cells such as adipocytes [63]. The polymorphisms of VDR may be associated with insulin resistance, which may lead to the risk of gestational diabetes mellitus (GDM) [64]. While a few studies have demonstrated a link between GDM and foetal macrosomia [65,66], a recent meta-analysis found that specific patterns of VDR polymorphisms influence birth weight and other anthropometric neonatal outcomes [38].…”
Section: Discussionmentioning
confidence: 99%